Electrochemical device and electronic device

By controlling the relative percentage content fluctuation value of silicon-based material particles and the content of binder in the negative electrode sheet of the electrochemical device, and adding fluorovinyl carbonate to the electrolyte, the volume expansion and contraction of the silicon-based material during the circulation process is solved, and the circulation performance and energy density of the electrochemical device are significantly improved.

CN119965218AActive Publication Date: 2025-05-09NINGDE AMPEREX TECHNOLOGY LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510130538.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2021-12-24
Publication Date
2025-05-09
Estimated Expiration
2041-12-24

AI Technical Summary

Technical Problem

When existing electrochemical devices use silicon-based materials as negative electrode active materials, there are problems of volume expansion and contraction, which leads to the generation of solid electrolyte boundary phase film and the consumption of lithium ions, which in turn affects the cyclic performance and energy density of the electrochemical device.

Method used

By controlling the relative percentage content fluctuation value of the silicon-based material particles and the content of the binder in the negative electrode active material layer of the negative electrode sheet, the weight loss rate of the negative electrode active material layer of the negative electrode sheet during heating is between 1.5% and 18%, and fluorovinyl carbonate is added to the electrolyte to optimize the distribution of the silicon-based material and the composition of the electrolyte.

Benefits of technology

The cycling performance, rate performance and expansion performance of the electrochemical device are significantly improved, the consumption of lithium ions and the generation of solid electrolyte boundary phase films are reduced, and the energy density and stability of the electrochemical device are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005261396090000131
    Figure BDA0005261396090000131
  • Figure BDA0005261396090000141
    Figure BDA0005261396090000141
  • Figure BDA0005261396090000151
    Figure BDA0005261396090000151
Patent Text Reader

Abstract

The invention provides an electrochemical device and an electronic device. The electrochemical device comprises a negative pole piece and an electrolyte, the negative pole piece comprises a negative active material layer, the negative active material layer comprises silicon-based material particles and a binder, and the negative pole piece satisfies: (B + C) / 7lt, alt; (B + C) / 1.8, A represents the weight loss ratio of the negative electrode active material layer of the negative electrode plate when the negative electrode active material layer is heated to 480 DEG C in an Ar atmosphere by taking the mass percent as the unit; b represents a relative percentage content fluctuation value of silicon elements in the silicon-based material particles; c represents the content of the silicon element in the negative pole piece by mass percent, 1.5% < = A < = 18%, 1% < = C < = 20%, the electrolyte comprises fluoroethylene carbonate, and the content X of the fluoroethylene carbonate by mass percent and the content C of the silicon element in the negative pole piece by mass percent meet the condition that X is greater than or equal to C. The negative pole piece satisfies (B + C) / 7lt; alt; and (B + C) / 1.8, so that the cycle performance, the rate capability and the expansion performance of the electrochemical device can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the application with the application number 202180031196.9, the application date of December 24, 2021, and the invention name of "Electrochemical Device and Electronic Device". Technical Field

[0002] This application relates to the field of electrochemical energy storage, and particularly to electrochemical devices and electronic devices. Background Art

[0003] With the development and progress of electrochemical devices (e.g., lithium-ion batteries), higher and higher requirements are put forward for their cycling performance and energy density. Currently, in terms of improving the energy density of electrochemical devices, using silicon-based materials in the negative electrode tab is the current trend. However, during the process of lithium deintercalation and intercalation in silicon-based materials, there is a large volume expansion and contraction, forming a large amount of new solid electrolyte interface film (SEI), consuming limited lithium ions and electrolyte in the electrochemical device, significantly increasing the impedance of the electrochemical device, and hindering the large-scale industrial application of silicon-based materials. Summary of the Invention

[0004] Some embodiments of this application provide an electrochemical device. The electrochemical device includes a negative electrode tab and an electrolyte. The negative electrode tab includes a negative electrode active material layer. The negative electrode active material layer includes silicon-based material particles and a binder. The negative electrode tab satisfies: (B + C) / 7 < A < (B + C) / 1.8, where A represents the weight loss rate of the negative electrode active material layer of the negative electrode tab at 480 °C in an Ar atmosphere in mass percentage; B represents the relative percentage content fluctuation value of silicon elements in the silicon-based material particles; C represents the content of silicon elements in the negative electrode tab in mass percentage. Among them, 1.5% ≤ A ≤ 18%, 1% ≤ C ≤ 20%. The electrolyte includes fluoroethylene carbonate, and the content X of fluoroethylene carbonate in mass percentage and the content C of silicon elements in the negative electrode tab in mass percentage satisfy: X ≥ C. By making the negative electrode tab satisfy (B + C) / 7 < A < (B + C) / 1.8, the cycling performance, rate performance, and expansion performance of the electrochemical device can be significantly improved.

[0005] In some embodiments, the weight loss rate A of the negative electrode active material layer of the negative electrode tab at 480 °C in an Ar atmosphere satisfies: 1.5% ≤ A ≤ 18%. If the value of A is too large, it indicates that there is too much binder in the negative electrode active material layer, which will inhibit lithium ion transmission, increase the polarization of the electrochemical device, and deteriorate the rate performance of the electrochemical device; if the value of A is too small, it indicates that there is too little binder in the negative electrode active material layer, which is not conducive to alleviating the volume expansion of the silicon-based material during cycling and deteriorates the cycling performance of the electrochemical device.

[0006] In some embodiments, the relative percentage content fluctuation value B of the silicon element in the silicon-based material particles satisfies: B<16%. If B is too large, it indicates that the uniformity of the silicon element is poor, which is not conducive to improving the cycle performance and expansion performance of the electrochemical device. In some embodiments, B≤10%.

[0007] In some embodiments, the content C of silicon in the negative electrode sheet in mass percentage satisfies: 1%≤C≤20%. If the value of C is too large, the silicon-based material will expand too much during the cycle, which is not conducive to the improvement of the cycle performance of the electrochemical device; if the value of C is too small, it is not conducive to the improvement of the energy density of the electrochemical device. In some embodiments, 1%≤C≤10%.

[0008] In some embodiments, the porosity P of the negative electrode sheet and the mass percentage C of the silicon element in the negative electrode sheet satisfy: P ≥ 15 × C 1 / 4 When the silicon content C in the negative electrode is larger in mass percentage, more pores are needed to alleviate the expansion of the silicon-based material. 1 / 4 When the volume expansion of silicon-based materials is reduced, it can effectively alleviate the volume expansion of silicon-based materials.

[0009] In some embodiments, the porosity P of the negative electrode sheet satisfies: 18% ≤ P ≤ 40%. When the porosity of the negative electrode sheet is too low, it is difficult for the electrolyte to fully infiltrate, which increases the transmission distance of lithium ions, deteriorates the kinetic performance of the electrochemical device, and is not conducive to alleviating the expansion of silicon-based materials during the cycle. When the porosity of the negative electrode sheet is too large, it is not conducive to improving the energy density of the electrochemical device.

[0010] In some embodiments, the content X of fluoroethylene carbonate in mass percentage and the content C of silicon in the negative electrode sheet in mass percentage satisfy: X ≥ C. When the FEC content in the electrolyte is greater than or equal to the content of silicon in the negative electrode sheet, the cycle performance, expansion performance and rate performance of the electrochemical device are better.

[0011] In some embodiments, the content X of fluoroethylene carbonate in mass percentage satisfies: 2%≤X≤20%. When the value of X is too small, the improvement effect of fluoroethylene carbonate on the cycle performance of the electrochemical device is relatively limited; when the value of X is too large, it indicates that the FEC content is too high, and too much FEC will reduce the mobility of lithium ions in the electrolyte and affect the rate performance of the electrochemical device. In some embodiments, 2%≤X≤10%.

[0012] In some embodiments, the silicon-based material particles include silicon and carbon. By embedding the silicon-based particles into the carbon matrix, direct contact between the silicon-based particles and the electrolyte is avoided, and repeated generation of SEI during the cycle is reduced, thereby reducing the loss of reversible lithium.

[0013] An embodiment of the present application further provides an electronic device, including the above-mentioned electrochemical device.

[0014] In the embodiment of the present application, by making the negative electrode sheet satisfy (B + C) / 7 < A < (B + C) / 1.8, from the perspective of the electrode sheet, the expansion of the silicon-based material can be limited within the range that the electrode sheet can withstand, significantly improving the expansion and deformation performance of the electrochemical device; from the perspective of the material, the lithium intercalation expansion of the silicon-based material is reduced, and the repeated generation and destruction of SEI on the surface of the silicon-based particles are reduced, significantly improving the cycle performance and rate performance of the electrochemical device. Detailed implementation manners

[0015] The following embodiments can enable those skilled in the art to understand the present application more comprehensively, but do not limit the present application in any way.

[0016] Some embodiments of the present application provide an electrochemical device, which includes a negative electrode sheet and an electrolyte. In some embodiments, the negative electrode sheet includes a negative electrode active material layer, and the negative electrode active material layer includes silicon-based material particles and a binder. In some embodiments, the binder can bond the silicon-based material particles together, reducing the degree of expansion and contraction of the silicon-based material particles during cycling.

[0017] In some embodiments, the negative electrode sheet satisfies: (B + C) / 7 < A < (B + C) / 1.8, where A represents the weight loss rate in mass percentage when the negative electrode active material layer of the negative electrode sheet is heated to 480 °C in an Ar atmosphere; B represents the fluctuation value of the relative percentage content of silicon element in the silicon-based material particles; C represents the content of silicon element in the negative electrode sheet in mass percentage. In some embodiments, the value of A can reflect the content of the binder to a certain extent. The larger A is, the more binder there is in the negative electrode active material layer, and the smaller A is, the less binder there is in the negative electrode active material layer. To reduce the deformation of the electrochemical device during cycling, there can be enough binder in the negative electrode sheet, but too much binder will inhibit lithium ion transport, increase the polarization of the electrochemical device, and deteriorate the rate performance of the electrochemical device. In some embodiments, the fluctuation value of the relative percentage content of silicon element in the silicon-based material particles represents the uniformity of the silicon element distribution. The larger the fluctuation value is, the worse the uniformity is. The distribution uniformity of silicon element has a significant correlation with the cycling performance and swelling performance of the electrochemical device. The higher the uniformity is, the more beneficial it is to reduce the stress generated by the swelling of the lithium ion battery, and the better the cycling performance and swelling performance of the electrochemical device are. In some embodiments, generally, as the content of silicon element in the negative electrode sheet in mass percentage increases, the energy density of the electrochemical device can be correspondingly improved. By making the negative electrode sheet satisfy (B + C) / 7 < A < (B + C) / 1.8, the cycling performance, rate performance and swelling performance of the electrochemical device can be significantly improved.

[0018] In some embodiments, the weight loss rate A of the negative electrode active material layer of the negative electrode sheet when heated to 480 °C in an Ar atmosphere satisfies: 1.5% ≤ A ≤ 18%. If the value of A is too large, it indicates that there is too much binder in the negative electrode active material layer, which will inhibit lithium ion transport, increase the polarization of the electrochemical device, and deteriorate the rate performance of the electrochemical device; if the value of A is too small, it indicates that there is too little binder in the negative electrode active material layer, which is not conducive to alleviating the volume expansion of the silicon-based material during cycling and deteriorates the cycling performance of the electrochemical device. In some embodiments, A can be 1.5%, 5%, 8%, 12%, 15%, 18% or any other suitable value.

[0019] In some embodiments, the fluctuation value B of the relative percentage content of silicon element in the silicon-based material particles satisfies: B < 16%. If B is too large, it indicates that the uniformity of silicon element is poor, which is not conducive to improving the cycling performance and swelling performance of the electrochemical device. In some embodiments, B can be 15%, 10%, 8%, 5% or smaller values. Preferably, B ≤ 10%.

[0020] In some embodiments, the content C of silicon in the negative electrode sheet in mass percentage satisfies: 1% ≤ C ≤ 20%. In some embodiments, if the value of C is too large, the silicon-based material expands too much during the cycle, which is not conducive to the improvement of the cycle performance of the electrochemical device; if the value of C is too small, it is not conducive to the improvement of the energy density of the electrochemical device. In some embodiments, C can be 1%, 5%, 10%, 15%, 20% or any other suitable value. Preferably, 1% ≤ C ≤ 10%.

[0021] In some embodiments, the porosity P of the negative electrode sheet and the mass percentage C of the silicon element in the negative electrode sheet satisfy: P ≥ 15 × C 1 / 4 The volume of silicon-based material particles expands by about 300% after lithium is embedded at room temperature. The huge volume expansion effect can easily lead to problems such as demolding and powder loss of the negative electrode. Reserving a certain amount of pores in the negative electrode can effectively alleviate the volume expansion of silicon-based materials. When the content C of silicon in the negative electrode in mass percentage is larger, more pores are needed to alleviate the expansion of silicon-based materials. When P≥15×C 1 / 4 When the volume expansion of silicon-based materials is reduced, it can effectively alleviate the volume expansion of silicon-based materials.

[0022] In some embodiments, the porosity P of the negative electrode sheet satisfies: 18% ≤ P ≤ 40%. When the porosity of the negative electrode sheet is too low, it is difficult for the electrolyte to fully infiltrate, which increases the transmission distance of lithium ions, deteriorates the kinetic performance of the electrochemical device, and is not conducive to alleviating the expansion of silicon-based materials during the cycle. When the porosity of the negative electrode sheet is too large, it is not conducive to improving the energy density and kinetic performance of the electrochemical device.

[0023] In some embodiments, the electrolyte is reduced at the negative electrode plate, and a SEI layer is generated on the surface of the negative electrode active material to stabilize the interface and delay the continuous consumption of reversible lithium. If the SEI is too thin, it is easy to break during the expansion of the negative electrode active material particles, generate a new interface, and deteriorate the cycle performance of the electrochemical device; if the SEI is too thick, the rate of charge transfer will be reduced, and the rate performance of the electrochemical device will be deteriorated. In some embodiments, the electrolyte includes fluoroethylene carbonate, and the content X of fluoroethylene carbonate in mass percentage and the content C of silicon element in the negative electrode plate in mass percentage satisfy: X≥C. Fluoroethylene carbonate (FEC) is an important film-forming additive in the electrolyte. The SEI generated by decomposition during the cycle isolates the negative electrode active material from further contact with the electrolyte, reduces the consumption of lithium ions, and has an improving effect on the cycle performance. When the FEC content in the electrolyte is greater than or equal to the content of silicon element in the negative electrode plate, the cycle performance, expansion performance and rate performance of the electrochemical device are better.

[0024] In some embodiments, the content X of fluoroethylene carbonate in mass percentage satisfies: 2%≤X≤20%. When the value of X is too small, the improvement effect of fluoroethylene carbonate on the cycle performance of the electrochemical device is relatively limited; when the value of X is too large, it indicates that the FEC content is too high, and too much FEC will reduce the mobility of lithium ions in the electrolyte and affect the rate performance of the electrochemical device. In some embodiments, X can be 2%, 5%, 10%, 12%, 15%, 20% or other suitable values. Preferably, 2%≤X≤10%.

[0025] In some embodiments, the silicon-based material particles include silicon and carbon, for example, silicon-carbon compounds or composites, for example, SiC. By embedding the silicon-based particles in the carbon matrix, direct contact between the silicon-based particles and the electrolyte is avoided, and the repeated generation of SEI during the cycle is reduced, thereby reducing the loss of reversible lithium.

[0026] In some embodiments, the preparation method of the silicon-based material can be prepared by the following preparation method: the porous carbon matrix is ​​placed in a rotary kiln, the furnace tube is purged with nitrogen at room temperature for 20 to 40 minutes, and then the temperature of the porous carbon matrix sample is increased to 450°C to 500°C. The nitrogen flow rate is adjusted so that the gas residence time in the rotary kiln is at least 90 seconds, and the flow rate is maintained for about 30 minutes. Then the gas supply is switched from nitrogen to a mixed gas of silicon-containing gas and nitrogen (the volume fraction of silicon-containing gas in the mixed gas is 5% to 30%). After deposition for 8 to 16 hours at a gas flow rate of 200 sccm to 400 sccm, nitrogen is continuously passed into the rotary kiln to blow out the silicon-containing gas from the furnace, and then the rotary kiln is purged for 30 minutes under nitrogen conditions, and then the rotary kiln is cooled to room temperature within 5 to 10 hours. Then, by converting the gas flow from nitrogen to air from a compressed air source, the nitrogen in the rotary kiln is gradually converted to air within 1 to 2 hours to obtain a silicon-based material.

[0027] In some embodiments, the porous carbon matrix can be selected from at least one of hard carbon, soft carbon, and graphite. For example, the hard carbon can include resin carbon, carbon black, organic polymer pyrolytic carbon, and combinations thereof. The soft carbon can include carbon fibers, carbon microspheres, and combinations thereof. The particle size of the porous carbon matrix is ​​not limited as long as the purpose of the present application can be achieved. For example, the particle size range of the porous carbon matrix is ​​3 μm. <Dv50<15μm。

[0028] The weight loss rate A of the negative electrode active material layer of the negative electrode sheet when heated to 480°C in an Ar atmosphere is related to the content of the binder in the negative electrode active material layer. For example, the more the amount of binder in the negative electrode active material layer, the greater A, and the less the amount of binder in the negative electrode active material layer, the smaller A. Based on this, A can be adjusted by adjusting the amount of binder.

[0029] The relative percentage content fluctuation value B of the silicon element in the silicon-based material particles is related to the uniformity of the pore distribution inside the carbon matrix and the pore size. For example, the more uniform the pore distribution inside the carbon matrix, the smaller B. Based on this, B can be adjusted by adjusting the pore distribution and pore size.

[0030] The mass percentage content C of silicon in the negative electrode plate is related to the amount of silicon-based material added in the negative electrode active material layer, wherein the silicon content deposited inside the silicon-based material can be adjusted by adjusting the deposition temperature, deposition time, and the concentration of the silicon-containing gas used. For example, C usually increases with the increase of deposition temperature, C usually increases with the increase of deposition time, and C usually increases with the increase of the concentration of the silicon-containing gas. Based on this, the mass content C of silicon in the negative electrode material layer can be adjusted.

[0031] The porosity of the negative electrode sheet usually decreases as the compaction density of the negative electrode sheet increases. Based on this, the porosity of the negative electrode sheet can be adjusted by adjusting the cold pressing pressure of the negative electrode sheet and adjusting the compaction density of the negative electrode sheet.

[0032] In some embodiments, the binder in the negative active material layer may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyvinyl pyrrolidone, polyaniline, polyimide, polyamideimide, polysiloxane, styrene-butadiene rubber, epoxy resin, polyester resin, polyurethane resin, or polyfluorene.

[0033] In some embodiments, the electrochemical device may include an electrode assembly, the electrode assembly including a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet. In some embodiments, the negative electrode sheet also includes a negative current collector. In some embodiments, the negative active material layer may be located on one side or both sides of the negative current collector. In some embodiments, the negative active material layer may also include a conductive agent. In some embodiments, the conductive agent in the negative active material layer may include at least one of nano-conductive carbon black, carbon nanotubes, carbon fibers, flake graphite, graphene, or Ketjen black. In some embodiments, the negative active material layer may also include negative active material graphite, that is, the negative active material layer may include silicon-based materials and graphite as negative active materials. In some embodiments, the mass ratio of the negative active material, the conductive agent, and the binder in the negative active material layer may be (78 to 98.5): (0.1 to 10): (0.1 to 10). It should be understood that the above is only an example, and any other suitable material and mass ratio may be used. In some embodiments, the negative current collector may be at least one of copper foil, nickel foil, or a carbon-based current collector.

[0034] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector, and the positive active material layer may include a positive active material. In some embodiments, the positive active material includes at least one of lithium cobaltate, lithium iron phosphate, lithium manganese iron phosphate, sodium iron phosphate, lithium vanadium phosphate, sodium vanadium phosphate, lithium vanadium phosphate, sodium vanadium phosphate, lithium vanadate, lithium manganate, lithium nickelate, lithium nickel cobalt manganate, lithium-rich manganese-based materials, or lithium nickel cobalt aluminum oxide. In some embodiments, the positive active material layer may also include a conductive agent. In some embodiments, the conductive agent in the positive active material layer may include at least one of conductive carbon black, ketjen black, lamellar graphite, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the positive active material layer may also include a binder, and the binder in the positive active material layer may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyvinyl pyrrolidone, polyaniline, polyimide, polyamide-imide, polysiloxane, styrene-butadiene rubber, epoxy resin, polyester resin, polyurethane resin, or polyfluorene. In some embodiments, the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode active material layer may be (80 to 99): (0.1 to 10): (0.1 to 10). In some embodiments, the thickness of the positive electrode active material layer may be 10 μm to 500 μm. It should be understood that the above description is only an example, and the positive electrode active material layer may adopt any other suitable material, thickness, and mass ratio.

[0035] In some embodiments, the positive electrode current collector may be Al foil, and of course, other current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive electrode current collector may be 1 μm to 50 μm. In some embodiments, the positive electrode active material layer may be coated only on a partial area of ​​the positive electrode current collector.

[0036] In some embodiments, the separator includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the stability of the battery through the shutdown effect. In some embodiments, the thickness of the separator is in the range of about 3 μm to 20 μm.

[0037] In some embodiments, the surface of the isolation membrane may further include a porous layer, the porous layer is disposed on at least one surface of the isolation membrane, the porous layer includes inorganic particles and a binder, the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. In some embodiments, the pores of the isolation membrane have a diameter in the range of about 0.01 μm to 1 μm. The binder of the porous layer is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the separator can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the separator, and enhance the adhesion between the separator and the pole piece.

[0038] In some embodiments, the electrolyte further includes a lithium salt, and the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB or lithium difluoroborate. Preferably, the lithium salt includes LiPF6.

[0039] In some embodiments, the electrolyte may also include a non-aqueous solvent. The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof. The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof. Examples of linear carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and a combination thereof. Examples of the cyclic carbonate compound are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or a combination thereof. Examples of the fluorinated carbonate compounds are 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or a combination thereof. Examples of carboxylate compounds are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, mevalonolactone, caprolactone, methyl formate or a combination thereof. Examples of ether compounds are dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran or a combination thereof. Examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or a combination thereof. The content of the non-aqueous solvent is not particularly limited as long as the purpose of the present application can be achieved. For example, the mass percentage of the above-mentioned other non-aqueous solvents is 67% to 86%, for example, 67%, 67.5%, 70%, 75%, 80%, 83%, 85%, 85.5%, 86% or any range therebetween.

[0040] In some embodiments, the electrochemical device includes a lithium-ion battery, but the application is not limited thereto.

[0041] In some embodiments of the present application, the electrode assembly of the electrochemical device is a wound electrode assembly, a stacked electrode assembly, or a folded electrode assembly. In some embodiments, the positive electrode sheet and / or the negative electrode sheet of the electrochemical device can be a multi-layer structure formed by winding or stacking, or a single-layer structure in which a single-layer positive electrode, a separator, and a single-layer negative electrode are stacked.

[0042] In some embodiments of the present application, taking a lithium-ion battery as an example, a positive electrode sheet, a separator, and a negative electrode sheet are wound or stacked in sequence to form an electrode assembly, and then encapsulated in, for example, an aluminum-plastic film, injected with an electrolyte, formed, and encapsulated to form a lithium-ion battery. Then, the prepared lithium-ion battery is subjected to a performance test.

[0043] Those skilled in the art will appreciate that the above-described method for preparing an electrochemical device (eg, a lithium-ion battery) is only an example, and other methods commonly used in the art may be used without departing from the disclosure of the present application.

[0044] Embodiments of the present application also provide electronic devices including the above-mentioned electrochemical devices. The electronic devices of the embodiments of the present application are not particularly limited, and they can be any electronic devices known in the prior art. In some embodiments, the electronic device can include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0045] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.

[0046] Comparative Example 1-1

[0047] Preparation of positive electrode sheet: Mix the positive electrode active materials lithium cobalt oxide, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) in a weight ratio of 97:1.4:1.6, add N-methylpyrrolidone (NMP) as a solvent, and stir evenly. The slurry (solid content of 72wt%) is evenly coated on the positive electrode current collector aluminum foil with a coating thickness of 80μm, dried at 85℃, and then cold pressed, cut, and slit, and dried under vacuum conditions at 85℃ for 4 hours to obtain the positive electrode sheet.

[0048] Preparation of silicon-based composite materials: A porous carbon substrate with a Dv50 of 10 μm is placed in a rotary kiln, the furnace tube is purged with nitrogen at room temperature for 30 minutes, and then the heating temperature of the porous carbon sample is increased to 450°C. The nitrogen flow rate is adjusted so that the gas residence time in the rotary kiln is at least 90 seconds, and maintained at this flow rate for 30 minutes. The gas supply is then switched from nitrogen to a mixed gas of silicon-containing gas (such as silane) and nitrogen, wherein the volume ratio of silicon-containing gas to nitrogen in the mixed gas is 5:95. After deposition for 8 hours at a gas flow rate of 200 sccm, nitrogen is continuously passed into the rotary kiln to blow out the silicon-containing gas from the furnace, and the rotary kiln is purged under nitrogen for 30 minutes, and then the rotary kiln is cooled to room temperature within several hours (e.g., 8 hours). Then, by switching the gas flow from nitrogen to air from a compressed air source, the nitrogen in the rotary kiln is gradually converted to air within 2 hours to obtain a silicon-based composite material, i.e., silicon-based particles. It has been determined that the relative percentage content fluctuation value B of the silicon element in the silicon-based material particles is 10%.

[0049] Preparation of negative electrode sheet: The silicon-based material, artificial graphite, binder polyacrylic acid and sodium carboxymethyl cellulose (CMC) prepared above are dissolved in deionized water in a weight ratio of 5.7:91.8:1:1.5 to form a negative electrode slurry (solid content is 40wt%). A 10μm thick copper foil is used as the negative electrode current collector, and the negative electrode slurry is coated on the negative electrode current collector with a coating thickness of 50μm, dried at 85°C, and then cold pressed, cut and slit, and dried under vacuum conditions at 120°C for 12 hours to obtain a negative electrode sheet.

[0050] Preparation of isolation film: The isolation film is 7 μm thick polyethylene (PE).

[0051] Preparation of electrolyte: In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) are mixed in a mass ratio of EC: PC: DEC = 1:1:1, dissolved and stirred thoroughly, and then lithium salt LiPF6 is added. After mixing evenly, an electrolyte is obtained in which the mass percentage of LiPF6 is 12.5%.

[0052] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package it, and obtain the lithium-ion battery through the process of formation, degassing, trimming, etc.

[0053] Other embodiments and comparative examples are based on the steps of comparative example 1-1 with parameter changes, and the specific changed parameters are described in the following table.

[0054] The test methods for various parameters of this application are described below.

[0055] 1. Porosity test of negative electrode: The porosity of negative electrode is tested by gas replacement method: Use the same mold to punch more than 50 electrodes with a radius of d, measure the thickness h of each electrode, and put them into the sample cup of the true density tester (AccuPycⅡ1340). Fill the electrode with He in the closed sample chamber, and measure the true volume V of the electrode. Finally, the porosity P of the electrode is obtained by the following formula: P = (1-V / πd 2 ×50×h)×100%.

[0056] 2. Test of silicon content in negative electrode plate: Place the negative electrode plate in a vacuum oven at 100°C and dry it for 24 hours. Use a blade to scrape off part of the active material layer on the negative electrode plate and weigh the mass M1. Then place the scraped active material layer in a continuous air atmosphere for heat treatment at 800°C to remove the carbonaceous material. The remaining material is weighed to obtain the mass M2. Finally, the silicon content C in the plate is obtained by the following formula: C = 0.467×M2 / M1.

[0057] 3. Test of the fluctuation value of the relative percentage content of silicon element in silicon-based material particles: Place the electrode in a vacuum oven at 100°C and dry it for 24 hours. Under a protective atmosphere, use a focused ion beam (FIB) to process the silicon-based material particles in the electrode into 50-100nm thin slices. Then, use the X-ray energy dispersive spectrometer (EDS) in a projection electron microscope (TEM) to scan the relative percentage content of silicon atoms in the silicon-based particles. The line scan position is selected at any position inside the silicon-based particles. The fluctuation value of the silicon element is the difference between the highest and lowest values ​​of the relative percentage content of silicon atoms in the entire line scan.

[0058] 4. Test for the content of fluoroethylene carbonate (FEC) in the electrolyte: The electrochemical device was discharged to a state of charge (SOC) of 0% and then centrifuged. The liquid obtained after centrifugation was subjected to GC-MS test to detect the percentage of FEC components.

[0059] 5. Test of weight loss rate of negative electrode active material layer in mass percentage when heated to 480°C in Ar atmosphere: Use a blade to scrape off part of the active material layer on the negative electrode plate and weigh the mass A1. Then place the scraped active material layer in Ar atmosphere and heat it to 480°C, and measure the mass A2. The weight loss rate A = (A1-A2) / A1.

[0060] 6. Cycle performance test: The test temperature is 25℃ and -10℃ respectively. Charge to 4.4V at 0.7C constant current, charge to 0.025C at constant voltage, and discharge to 3.0V at 0.5C after standing for 5 minutes. The capacity obtained at this time is taken as the initial capacity, and the cycle test is carried out at 0.7C charge / 0.5C discharge. The capacity after 400 cycles at 25℃ / -10℃ is taken as the actual capacity, and the capacity retention rate = actual capacity / initial capacity.

[0061] 7. Rate performance test: At 25°C, discharge to 3.0V at 0.2C, let stand for 5 minutes, charge to 4.45V at 0.5C, charge to 0.05C at constant voltage and let stand for 5 minutes, adjust the discharge rate, and perform discharge tests at 0.2C and 2.0C to obtain the discharge capacity respectively. Divide the capacity obtained at 2C rate by the capacity obtained at 0.2C to obtain the rate performance.

[0062] 8. Deformation rate test: Use a screw micrometer to test the thickness h1 of a fresh lithium-ion battery when it is half-charged. When it is cycled to 400 times, the lithium-ion battery is in a fully charged state. Use a screw micrometer to test the thickness h2 of the lithium-ion battery at this time. The deformation rate of the lithium-ion battery = (h2-h1) / h1.

[0063] It should be understood that the testing of the above parameters of lithium-ion batteries is a technology well known to those skilled in the art and will not be described in detail here. The testing method is not limited to the method described in this application, and other suitable testing methods may also be used.

[0064] Comparative Examples 1-1 to 1-10 and Examples 1-1 to 1-15:

[0065] The preparation methods of Comparative Examples 1-2 to 1-10 and Examples 1-1 to 1-15 are the same as the preparation method of Comparative Example 1-1, except that the corresponding parameters are adjusted to make the values ​​of A, B and / or C different.

[0066] Table 1:

[0067]

[0068] It can be seen by comparing Examples 1-1 to 1-3 with Comparative Examples 1-1 to 1-2 that when the content C of silicon element in the negative electrode sheet and the uniformity B of the distribution of silicon element within the silicon-based material particles are constant, as the weight loss rate A increases, the cycle capacity retention rate of the lithium-ion battery first increases and then decreases, the deformation rate of the lithium-ion battery first decreases and then increases, and the rate performance of the lithium-ion battery first increases and then decreases. This is because the higher the value of A, the stronger the adhesion of the negative electrode sheet, the higher the stability of the SEI on the surface of the silicon-based material particles, and the better the protection of the silicon-based material during the cycling process. However, when A is too high, the cycle capacity retention rate, deformation rate, and rate performance of the lithium-ion battery are affected. This is because excessive amounts of binder and SEI will inhibit lithium-ion transport and increase the polarization effect of the lithium-ion battery. The same conclusion can be obtained by comparing Comparative Examples 1-3 to 1-4 with Examples 1-4 to 1-6, or by comparing Comparative Examples 1-5 to 1-6 with Examples 1-7 to 1-9, or by comparing Comparative Examples 1-7 to 1-8 with Examples 1-10 to 1-12, or by comparing Comparative Examples 1-9 to 1-10 with Examples 1-13 to 1-15.

[0069] In addition, the higher the content of silicon element in the negative electrode sheet, the lower the uniformity of the distribution of silicon element within the silicon-based material, and the more binder and SEI are required. When it satisfies the inequality: (B + C) / 7 < A < (B + C) / 1.8, the capacity retention rate, deformation rate, and rate performance of the lithium-ion battery are improved.

[0070] Examples 2-1 to 2-10:

[0071] The preparation methods of Examples 2-1 to 2-10 are the same as those of Example 1-2, except that the corresponding parameters are adjusted to make the porosity P of the negative electrode sheet and / or the value of the content C of silicon element in the negative electrode sheet different.

[0072] Table 2:

[0073]

[0074] After lithium intercalation at room temperature, the volume of the silicon-based material particles expands by about 300%. The huge volume effect easily leads to problems such as delamination and powder shedding of the negative electrode active material layer. Reserving a certain amount of porosity in the negative electrode sheet can effectively alleviate the volume expansion of the silicon-based material. When the porosity of the negative electrode sheet is too low, the electrolyte is difficult to fully infiltrate the negative electrode sheet, increasing the lithium-ion transport distance and deteriorating the kinetic performance of the lithium-ion battery. By comparing Example 1-2 with Examples 2-1 to 2-10, it can be known that the porosity P of the negative electrode sheet and the content C of silicon element in the negative electrode sheet satisfy the following relational expression: P > 15×C 1 / 4 When this condition is met, the cycle capacity retention rate and deformation rate of the lithium-ion battery at room temperature and low temperature are both improved.

[0075] Embodiment 3-1 to 3-5:

[0076] The preparation methods of Examples 3-1 to 3-5 are the same as those of Examples 2-6, except that a certain amount of fluoroethylene carbonate is added to the electrolyte. The only difference is that the content X of fluoroethylene carbonate in the electrolyte and / or the content C of silicon in the negative electrode are different.

[0077] Table 3:

[0078]

[0079] In Table 3, “ / ” indicates that there is no corresponding preparation parameter.

[0080] Fluoroethylene carbonate (FEC) is an important film-forming additive in the electrolyte. The SEI generated by decomposition during the cycle isolates the negative electrode active material from further contact with the electrolyte, reduces the consumption of lithium ions, and plays an important role in the cycle performance of lithium-ion batteries. By comparing Example 1-1, Example 3-1 to Example 3-5, it can be seen that after adding FEC to the electrolyte, when the FEC content in the electrolyte is greater than or equal to the silicon content in the negative electrode plate, the cycle capacity retention rate and deformation rate of the lithium-ion battery at room temperature and low temperature are improved. However, the FEC content cannot be too high, because the addition of too much FEC will reduce the mobility of lithium ions in the electrolyte, affect the rate performance, and the deformation rate of the lithium-ion battery increases, and the capacity retention rate at low temperature is also reduced.

[0081] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features. For example, the above features are replaced with the technical features with similar functions disclosed in the present application.

Claims

1. An electrochemical device, wherein: include: A negative electrode plate, the negative electrode plate comprising a negative electrode active material layer, the negative electrode active material layer comprising silicon-based material particles and a binder, the negative electrode plate meeting the following requirements: (B+C) / 7 <A<(B+C) / 1.8, Wherein, A represents the weight loss rate of the negative electrode active material layer of the negative electrode plate when heated to 480° C. in an Ar atmosphere in units of mass percentage; B represents the relative percentage content fluctuation value of the silicon element in the silicon-based material particles; C represents the content of the silicon element in the negative electrode plate in units of mass percentage; The weight loss rate A of the negative electrode active material layer of the negative electrode plate when heated to 480° C. in an Ar atmosphere satisfies: 1.5%≤A≤18%; The content C of silicon in the negative electrode plate in mass percentage satisfies: 1%≤C≤20%; The electrochemical device also includes an electrolyte, the electrolyte includes fluoroethylene carbonate, and the content X of the fluoroethylene carbonate in mass percentage and the content C of the silicon element in the negative electrode plate in mass percentage satisfy: X≥C.

2. The electrochemical device according to claim 1, wherein: The relative percentage content fluctuation value B of the silicon element in the silicon-based material particles satisfies: B<16%.

3. The electrochemical device according to claim 1, wherein The porosity P of the negative electrode plate and the mass percentage C of the silicon element in the negative electrode plate satisfy: P>15×C 1 / 4 .

4. The electrochemical device according to claim 3, wherein: The porosity P of the negative electrode sheet satisfies: 18%≤P≤40%.

5. The electrochemical device according to any one of claims 1 to 4, wherein: The content X of the fluoroethylene carbonate in mass percentage satisfies: 2%≤X≤20%.

6. The electrochemical device according to any one of claims 1 to 4, wherein: B≤10%。 7. The electrochemical device according to any one of claims 1 to 4, wherein: 1%≤C≤10%。 8. The electrochemical device according to claim 5, wherein: 2%≤X≤10%。 9. The electrochemical device according to any one of claims 1 to 4, wherein: The silicon-based material particles include silicon and carbon.

10. An electronic device, wherein: Comprising the electrochemical device according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Negative electrode active material and battery

    CN112310360A

  • Electrochemical device and electronic device comprising the same

    CN112753116A

  • Negative pole piece, electrochemical device and electronic device

    CN113711385A

  • Electrochemical device and electronic device comprising same

    WO2021174442A1

  • Electrochemical device and electronic device comprising same

    WO2021174444A1